2018
DOI: 10.1039/c7ee03365f
|View full text |Cite
|
Sign up to set email alerts
|

A multifunctional polymer electrolyte enables ultra-long cycle-life in a high-voltage lithium metal battery

Abstract: We demonstrate a bacterial cellulose supported multifunctional polymer electrolyte for a 4.45 V-class LiCoO2 lithium metal battery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
145
0
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 285 publications
(147 citation statements)
references
References 37 publications
0
145
0
1
Order By: Relevance
“…As a result, PAMM/PET gel polymer electrolyte possessed electrochemical stability window exceeding 5 V (versus Li + /Li), ionic conductivity of 6.79 × 10 −4 S cm −1 at room temperature, high mechanical strength up to 27.5 MPa, and excellent interface compatibility with Li and LiNi 0.5 Mn 1.5 O 4 . Consequently, high‐voltage LiNi 0.5 Mn 1.5 O 4 /Li and LiNi 0.5 Mn 1.5 O 4 /Li 4 Ti 5 O 12 cells using PAMM/PET gel polymer electrolyte delivered stable charging/discharging profiles and excellent rate performances at both 25 and 55 °C . Particularly, LiNi 0.5 Mn 1.5 O 4 /PAMM/PET/Li cell (3.5–5 V) maintained 104 mAh g −1 of discharge capacity (78.9% of capacity retention) at 0.1 °C and room temperature after 500 cycles, indicating PAMM/PET gel polymer electrolyte was a promising polymer electrolyte for 5 V‐class lithium battery.…”
Section: Other Novel Polymer‐based Electrolytementioning
confidence: 96%
See 1 more Smart Citation
“…As a result, PAMM/PET gel polymer electrolyte possessed electrochemical stability window exceeding 5 V (versus Li + /Li), ionic conductivity of 6.79 × 10 −4 S cm −1 at room temperature, high mechanical strength up to 27.5 MPa, and excellent interface compatibility with Li and LiNi 0.5 Mn 1.5 O 4 . Consequently, high‐voltage LiNi 0.5 Mn 1.5 O 4 /Li and LiNi 0.5 Mn 1.5 O 4 /Li 4 Ti 5 O 12 cells using PAMM/PET gel polymer electrolyte delivered stable charging/discharging profiles and excellent rate performances at both 25 and 55 °C . Particularly, LiNi 0.5 Mn 1.5 O 4 /PAMM/PET/Li cell (3.5–5 V) maintained 104 mAh g −1 of discharge capacity (78.9% of capacity retention) at 0.1 °C and room temperature after 500 cycles, indicating PAMM/PET gel polymer electrolyte was a promising polymer electrolyte for 5 V‐class lithium battery.…”
Section: Other Novel Polymer‐based Electrolytementioning
confidence: 96%
“…In order to improve electrolyte stability and reduce electrode/electrolyte interfacial reactivity of high voltage LiNi 0.5 Mn 1.5 O 4 batteries, a cross‐linking polymer electrolyte composed by poly(acrylic anhydride), poly(methyl methacrylate), and PET membrane (PAMM/PET) was fabricated via in situ polymerization . The anhydride and acrylate groups in cross‐linking PAMM provided high voltage resistance and fast ionic conductivity; meanwhile, the cross‐linking structure and PET membrane were beneficial to the mechanical property.…”
Section: Other Novel Polymer‐based Electrolytementioning
confidence: 99%
“…However, owing to the insolubility in organic solvents, natural polymers are generally difficult to use directly as gel polymer skeletons to reserve organic liquid electrolytes in conventional Li batteries. Modification strategies through grafting or combining with other macromolecules have also been demonstrated . For instance, by combining starch with γ‐(2,3‐epoxypropoxy)propyltrimethoxysilane, organic electrolyte can be gelled via the chemical substitution reaction between ─OH groups and ─Si─(OCH 3 ) 3 (Figure A,B) .…”
Section: Natural Primordial Biological Polymersmentioning
confidence: 99%
“…For instance, by combining starch with γ‐(2,3‐epoxypropoxy)propyltrimethoxysilane, organic electrolyte can be gelled via the chemical substitution reaction between ─OH groups and ─Si─(OCH 3 ) 3 (Figure A,B) . Recently, Dong et al reported a new kind of bio‐based poly (methyl vinyl ether‐alt‐maleic anhydride) composite electrolyte layer supported by natural bacterial cellulose and demonstrated its effectiveness in Li metal anode protection . In addition, electrolyte gelation can be also achieved by the doping oleic acid and glycerol plasticizer into carboxymethyl cellulose, the reinforcement of gelatin protein toward polyethylene oxide (PEO) electrolyte, the cross‐linking polymerization of functionalized lignin‐derivatives, vanillyl alcohol, and gastrodigenin with multifunctional thiol monomers, and the recombination of inorganic molybdenum disulfide (MoS 2 ) nanoflakes with surfactant‐oxidized cellulose nanocrystal (OCNC) .…”
Section: Natural Primordial Biological Polymersmentioning
confidence: 99%
“…Dong et al. reported a bacterial cellulose supported poly(methyl vinyl ether‐alt‐maleic anhydride) composite electrolyte (PMM‐CPE, Scheme b) with high ionic conductivity and wide electrochemical window . This GPE could stabilize lithium anode and LiCoO 2 cathode simultaneously by forming favorable SEI/CEI layers, delivering excellent capacity retention and rate performance.…”
Section: Gel Polymer Electrolytementioning
confidence: 99%